Rechtsvacuum Phenomenon in Government Regulation of the Republic of Indonesia Number 51 of 2020 related to Passport Renewal Period to 10 Years - Fachrizza Sidi Pratama (Journal of Law and Border Protection, 2019)
Legislation is one of the legal products issued by the state government component. In this case, the laws and regulations include the Constitution of the Republic of Indonesia year 1945, the Decree of the People's Consultative Assembly, The Law / Regulation of the Government In lieu of Laws, Government Regulations, Presidential Regulations, and Local Regulations. As for its application, the rules have levels in the arrangement, where there are sections that explain macro and its derivatives that are narrowing down to the implementing regulations. The levels of the rules must be complete because each of them has its own function. Meanwhile, in this journal, there will be a discussion on the phenomenon of legal vacancies in the case study of Government Regulation of the Republic of Indonesia Number 51 of 2020 related to the Period of Extending Passports to 10 Years, where in the issuance of government regulations have not been included implementing regulations that will regulate how the implementation of government regulations in the field.